Financial Inclusion and Legal Discrimination Against Women : Evidence from Developing Countries - Demirguc-Kunt, Asli; Klapper, Leora; Singer, Dorothe (World Bank, Washington, DC, 2013)
This paper documents and analyzes gender differences in the use of financial services using individual-level data from 98 developing countries. The data, drawn from the Global Financial Inclusion (Global Findex) database, highlight the existence of significant gender gaps in ownership of accounts and usage of savings and credit products. Even after controlling for a host of individual characteristics including income, education, employment status, rural residency and age, gender remains significantly related to usage of financial services. This study also finds that legal discrimination against women and gender norms may explain some of the cross-country variation in access to finance for women. The analysis finds that in countries where women face legal restrictions in their ability to work, head a household, choose where to live, and receive inheritance, women are less likely to own an account, relative to men, as well as to save and borrow. The results also confirm that manifestations of gender norms, such as the level of violence against women and the incidence of early marriage for women, contribute to explaining the variation in the use of financial services between men and women, after controlling for other individual and country characteristics.